Extraction optimization and structural characterization of pectin from persimmon fruit (Diospyros kaki Thunb. var. Rojo brillante). (15th November 2021) - Muñoz-Almagro, Nerea; Vendrell-Calatayud, Mario; Méndez-Albiñana, Pablo; Moreno, Rodrigo; Cano, M. Pilar; Villamiel, Mar
Abstract: In this work we have efficiently extracted and characterized pectin from different tissues of astringent (AS) and non-astringent (NAS) persimmon fruits (peel, pulp, whole fruit) for the first time. The highest pectin extraction (≥7.2%) was carried out at 80 °C, 120 min with 1.5% sodium citrate in peel of both AS and NAS persimmon samples. All persimmon pectins showed a molecular weight and galacturonic acid content upper than 328 kDa and 78%, respectively, indicating their suitability as food ingredient. Pectin extracted from AS pulp and peel tissues exhibited an enriched structure in rhamnose and arabinose, whereas the opposite behavior was observed in NAS persimmon whole fruit samples. Remarkably, both pulp tissues (AS and NAS) presented the highest levels of glucose and mannose, non-pectic carbohydrates. In addition, techno-functional assessment (zeta potential, particle size, apparent viscosity, gelation) showed the suitability of the persimmon pectins for a broad range of industrial applications. Graphical abstract: Unlabelled Image Highlights: Pectin from astringent and non-astringent persimmon var. Rojo brillante was obtained. The highest pectin yield was found in the peel of non-astringent fruits. Galacturonic acid was found to be close to 78% in all tissues analysed. Rhamnogalacturonan I was more abundant in pulp and whole sample in astringent fruits. Pectin from persimmon var. Rojo brillante was of low-methoxyl degree.